STUDY ON INCREASING THE EFFICIENCY IN VOLLEYBALL - ȚURCANU, Florin; ȚURCANU, Dana Simona (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2016)
Starting from the analysis of the current global performance context in volleyball and our internal realities, we consider it appropriate to conceptually address the optimization strategy of the Romanian volleyball performance, by comparing the results of the second attack line, between two Romanian teams and one from the Italian championship and reporting them to the efficient result of an official volleyball match. The theme follows the progress of the volleyball game by aligning internal performance strategies to modern game trends that are based on surprising the opponent. Regarding the preparation and training area of volleyball, along with methodological orientation in modelling the content of preparation, it is necessary to implement in the collective and tactical structure of the second line of attack the element of surprise in the approach of an official game. The initiative represents a starting point for current and prospective coaches who want to improve the quality of the game, using the attack in the second line.